Comparação entre rotas tradicionais de beneficiamento de minérios para a concentração de alumínio metálico em escórias - Santos, Joel Martins dos (2013)
The final step of recycling aluminum, after collection, classification and cleaning is its transformation into commercial alloy using recycled metal and its chemical correction. One of the relevant impacts in this process is the creation of slags that represent one of the main cost factors. The slag is a byproduct that appears on the surface of liquid metal due to its oxidation, from the presence of impurities in the scraps and in addition of salts fluxes. Usually they are rich in metallic aluminum in the form of small droplets which are captured inside and can lead to a considerable loss of productivity. By its content in metallic aluminum, these slags have market value for industries specialized in recovery, usually with pyrometallurgy technique. However slim granulometries fractions, smaller than 0.15 mm, bring difficulties for the recovery of aluminum contained. This paper investigated two traditional routes of ore improvement in order to evaluate the concentration of the aluminum contained into the aluminum slags: (I) attrition in tumbling barrel and (II) crushing. In both were used a sequence of auxiliary operation for granulometric distribution. In order to compare its efficiency between the two routes it was verified, in both, the concentration of aluminum present into the granulometric products obtained. Another comparative factor was the energetic indicator denominated by WI (Work Index). This parameter is a characteristic from the industries of mineral processing and it represents the energy consumed by the techniques or routes applied. For the characterization of concentrated aluminum on the two routes techniques used were wet-way with measurement of hydrogen, x-ray fluorescence and induction furnace pyrometry. The evaluation for the concentrated revealed an increase of metallic aluminum contained as occurred into the particle size reduction of the enhacing material in its recovery.